Mercury intoxication and ophthalmic involvement: An update review - de los Santos, Cristian; Pastor, J. Carlos; Calonge, Margarita (Frontiers in Toxicology, 2023)
Human intoxication after mercury exposure is a rare condition that can cause severe damage to the central nervous, respiratory, cardiovascular, renal, gastrointestinal, skin, and visual systems and represents a major public health concern. Ophthalmic involvement includes impaired function of the extraocular muscles and the eyelids, as well as structural changes in the ocular surface, lens, retina, and optic nerve causing a potential irreversible damage to the visual system. Although, there are many pathways for poisoning depending on the mercury form, it has been suggested that tissue distribution does not differ in experimental animals when administered as mercury vapor, organic mercury, or inorganic mercury. Additionally, visual function alterations regarding central visual acuity, color discrimination, contrast sensitivity, visual field and electroretinogram responses have also been described widely. Nevertheless, there is still controversy about whether visual manifestations occur secondary to brain damage or as a direct affectation, and which ocular structure is primarily affected. Despite the use of some imaging techniques such as in vivo confocal microscopy of the cornea, optical coherence tomography (OCT) of the retina and optic nerve, and functional tests such as electroretinography has helped to solve in part this debate, further studies incorporating other imaging modalities such as autofluorescence, OCT angiography or adaptive optics retinal imaging are needed. This review aims to summarize the published structural and functional alterations found in the visual system of patients suffering from mercury intoxication.